Implementation of Contextual Learning Models for Children's Cognitive Development in Group A RA Miftahul Ulum Sumber Jaya Kintap Tanah Laut, South Kalimantan - Robiatul Adawiyah (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
The aim of this study is to determine the implementation of contextual learning models for children's cognitive development to support children's cognitive development. The type of research used is a descriptive qualitative approach using observation methods, interviews and documentation as data collection techniques. Based on the research results, it shows that the application of a contextual learning model that links teaching material with children's real-world experiences is able to link active involvement, logical thinking, and also solve simple problems in playing and learning activities. Teachers facilitate the learning process through linkage strategies (relating), direct experience (expriencing), application (applying), group work (cooperating), saera reflection (reflecting). This finding is an effective approach in stimulating children's overall cognitive development, because it is able to provide a learning environment that is meaningful, relevant, and appropriate to the stage of early childhood development.